MODEL FENOLOGI TANAMAN KELAPA SAWITA PHENOLOGY MODEL OF PALMOIL - Fadjry Djufri; I. Handoko; Yonny Koesmaryono (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2000)
Abstract is available in the full text (pdf format)